Strategies for Reducing Defect Rates in Commercial Feed Production Using the RCA, FMEA, and 5W+1H Methods in the Feed Industry at PT XYZ - Reina Anindita Putri; Akmal Suryadi (Yayasan Kita Menulis, 2025)
The high level of defects in feed production, especially related to particle size (particle out of standard) is the main focus of this research because it has a significant impact on the quality of the final product and customer satisfaction. To overcome these problems, this research uses the Root Cause Analysis (RCA) method to identify the root causes of the problem, Failure Mode and Effect Analysis (FMEA) to determine risk priorities based on the Risk Priority Number (RPN) value, and the 5W+1H approach to provide implementable improvement proposals for the factors that cause defects. The results show that the dominant defect is caused by the clogged boiler duct factor with an RPN value of 200 which is the top priority in improvement efforts. The proposed improvement recommendations include conducting routine inspection and cleaning of boiler lines, as well as creating a checklist and cleaning schedule to ensure boiler lines remain clean and free from blockages. The implementation of this strategy is expected to reduce the level of defects so as to improve the efficiency of the production process and support the company's competitiveness in the animal feed industry.